The Expanding Role of Anti-Ku in Autoimmune Disorders - Mohammad, Adawi; Awni, Yousef; Ahlam, Adawi (Archives of Clinical and Biomedical Research, 2025)
Anti-Ku antibodies, directed against the Ku heterodimer (p70/p80), have emerged as significant biomarkers in a spectrum of autoimmune diseases, including systemic lupus erythematosus (SLE), polymyositis/ dermatomyositis (PM/DM), and mixed connective tissue disease (MCTD) [1]. This review explores the expanding clinical implications of anti-Ku, its role in immune system dysregulation, and its association with organ-specific manifestations—particularly in muscular, pulmonary, and cutaneous involvement [2]. The presence of anti-Ku is increasingly linked to overlap syndromes, interstitial lung disease, and resistant forms of inflammatory myopathies [3]. Despite its diagnostic potential, challenges remain regarding its pathogenic relevance and therapeutic targeting [4]. Advances in detection methods, clinical cohort analyses, and immunopathological correlations underscore the need for further research to clarify anti-Ku's role as a prognostic and therapeutic biomarker in systemic autoimmune disorders [5].